1980
DOI: 10.1136/bjo.64.6.440
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cyst of the iris following penetrating keratoplasty.

Abstract: SUMMARY In a 35-year-old patient with keratoconus a cyst of the iris was first observed 22 months after routine penetrating keratoplasty. The lesion was completely excised and shown by light and transmission electron microscopy to be composed of conjunctival epithelium organised as a single large cyst containing serous material and occasional free epithelial cells. The management of epithelial implantation cysts is discussed. When indicated, complete surgical excision without rupture is preferred to avoid poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Complication of PKP include graft rejection or failure, graft dehiscence, infection, flat anterior chamber, pupillary block, synechial angle closure, aqueous misdirection, hyphema, cataract, retinal detachment, choroidal effusion, suprachoroidal hemorrhage, and endophthalmitis [17][18][19][20][21][22][23][24][25][26][27]. One of the more common complications after PKP is the development of glaucoma, which may occur either early or late postoperatively [28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…Complication of PKP include graft rejection or failure, graft dehiscence, infection, flat anterior chamber, pupillary block, synechial angle closure, aqueous misdirection, hyphema, cataract, retinal detachment, choroidal effusion, suprachoroidal hemorrhage, and endophthalmitis [17][18][19][20][21][22][23][24][25][26][27]. One of the more common complications after PKP is the development of glaucoma, which may occur either early or late postoperatively [28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…Echolucent cysts are always unilateral and are usually located in the iris or ciliary body stroma. They tend to have large diameters that cause iris atrophy by compression, as seen in this case [ 11 ]. In a retrospective chart review, Marigo et al [ 9 ] reported that most cystic lesions were not septate.…”
Section: Discussionmentioning
confidence: 99%
“…1 The debris material was whitish in color and could been seen on gonioscopy through the epithelial lining of the cyst (Figure 1B), and the fluid-debris level may represent serous material with free iris epithelial cells. 8 Occasionally, iris stromal cysts have been known to regress spontaneously. 9 Diathermy, electrolysis, aspiration followed by injection of absolute alcohol, and surgical excision with or without adjunctive cryotherapy and laser photocoagulation are therapeutic approaches that have been described should an iris stromal cyst become symptomatic.…”
Section: Discussionmentioning
confidence: 99%